Adsorption Equilibrium of Methylene Blue By Activated Carbon From Post-Anthesis Male Flower Palm Oil Waste - Yuli Ristianingsih; Indriana Lestari; Alit Istiani (Eksergi, 2022)
Methylene blue (MB) is wastewater from the textile industry. This dye is difficult to degrade naturally because it has a benzene group in its chemical chain. There are several ways to reduce waste, one of the economical ways is by using adsorption. In this study, MB was adsorbed using activated carbon from post-anthesis male flower palm oil (PAMF) waste which was activated using potassium hydroxide (KOH). The adsorption process was carried out at various temperatures (30, 40, and 50℃). The results showed that the addition of a KOH activator could increase the sorption capacity of methylene blue by 25.64%. The optimum temperature is suitable for the adsorption process of methylene blue with activated carbon of PAMF waste activated by KOH at a temperature of 30℃ with an adsorption capacity of 58.4793%. The adsorption equilibrium mechanism was studied using two types of adsorption isotherm models, namely the Langmuir and Freundlich models. Based on the data obtained, the MB adsorption process on activated carbon was compatible with the Freundlich model an R2 of 0.9557.